Avaliação da qualidade de vida em pacientes com doenças reumáticas tratados com agentes biológicos: uma coorte prospectiva - Haliton Alves de Oliveira Junior (2018)
The rheumatic conditions rheumatoid arthritis (RA), psoriatic arthritis (PsA) and ankylosing spondylitis (AS) are chronic inflammatory diseases that, if not properly treated, can lead to joint deformity and destruction and functional limitation, with a direct impact on patients quality of life. Health-Related Quality of life -HRQoL is a very broad concept, which can be simplified as the impact of health on a functional ability of an individual and the well-being perceived in the physical, mental and social life. This study aimed to evaluate the quality of life in a cohort of patients with chronic rheumatic autoimmune diseases using biological agents, through a generic instrument EuroQol - 5 Dimensions (EQ-5D). Data were collected through a standardized form developed by the Research Group on Pharmacoepidemiology (GPFE) to collect information regarding the use of drugs and adverse reactions, comorbidities, activity measures of rheumatic conditions and evaluation of the functionality and quality of life. The interviews were conducted with those individuals who had their drug application processes approved and who accepted to participate in the survey (convenience sampling). The interviews were conducted in three stages: first interview (first dispensation), second interview (at least six months after the completion of the first interview) third interview (at least six months after the completion of the second interview). By January 2017, 595 patients who received initial provision of anti-TNF agents in the Brazilian Public Health System (SUS) and agreed to participate in the interviews were included in the study. The population consisted of 412 (69.2%) RA patients, 107 (18.0%) AS patients and 76 (12.8%) PsA patients. The most frequently used biological agent was adalimumab 330 (55.5%). Most of the population was composed by women 447 (75.1%). The mean ± SD duration of disease was 10.31±9.47 years and 119 (20.0%) patients had early disease. The women were in average older than men (p = 0.008) and a had lower proportion of early disease (p < 0.001). Women presented high disease activity by the Clinical Disease Activity Index (CDAI) (> 22) while men shown moderate disease activity (p <0.001). Also, women presented worse baseline quality of life and functionality than men (p = 0.001 and p <0.001, respectively for EQ-5D and Health Assessment Questionnaire (HAQ-DI). After 12 months of follow up, 353 patients completed all three interviews with a mean followup time in months of 6.69 ± 2.02; 7.04 ± 2.14 e 13.75 ± 2.30, respectively, for the intervals between visit 1 and visit 2, visit 2 and visit 3, and visit 1 and visit 3. After six and 12 month follow-up, quality of life improved significantly for this patients (p <0.05), independently of rheumatic disease or drug therapy (monotherapy or combination). Intenton-to-treat analysis by multiple imputation showed similar results. Compared with baseline, all of the EQ-5D domains, plus the Visual Analogue Scale (VAS) achieved significant improvements after 12 months of study. Multiple regression analysis by mied-effect model showed that white patients without comorbidities and with better baseline quality of life and functionality, improved more after 12 months of study. A sensitivity analysis by disease group presented the same results. However, patients with worse value of EQ5D at the beginning increased by 0.18 ± 0.21 the utility value until month 12, while the increase was 0.03 ± 0.15 for those patients with better utility values at baseline. Patients with a poor functionality at baseline (HAQ-DI> 1.4) increased by 0.13 ± 0.23 EQ-5D score after 12 months, while in patients with better functionality at baseline this augment was just 0.09 ± 0.17. The results of baseline distribution of variables show that the patients included in our study present mean age, disease duration, disease activity, quality of life and functionality similar with other national and international publications. In addition, knowing the association of the presence of HLA-B27 antigen in populations with spondyloarthritis, we noticed a higher prevalence of white individuals in these cohorts, which is also confirmed by other studies conducted with these populations. RA was the oldest cohort, with a longer duration of the disease, lower rate of early detection and a higher proportion of women; while AS was the youngest cohort, with shorter duration of disease, higher rate of early detection and higher proportion of men. These results for RA and AS cohorts are also shown by several other publications at international level. Our study showed that there was a clinically significant gain in quality of life in the rheumatic disease cohorts evaluated. In addition, our work showed that there was improvement in all the EQ-5D domains, with a clear reduction in the proportion of patients with problems in each of them, being the domain of pain and malaise the one that most influences the quality of life . Studies conducted in Europe show similar results of gain in quality of life and improvement in the domains of EQ-5D, evidencing the positive effect of biological therapy on the pathophysiology of immune-mediated rheumatic conditions. This study showed that, despite the high disease activity and low baseline quality of life and functionality, the use of biological agents therapy, associated or not with Synthetic Disease Modifying Rheumatic Drugs (sDMARDS), promoted a significant gain in quality of life over 12 months of follow-up. These results reaffirm the importance of a public policy aimed at guaranteeing the integrality of treatment, subsidizing decision-making processes in the collective health context and serving as a support for future research in the field of health economics.